Age-dependent changes in structure and function of the male labial gland in Bombus terrestris - Sobotník, Jan; Kalinová, Blanka; Cahlíková, Lucie; Weyda, Frantisek; Ptácek, Vladimír; Valterová, Irena (Journal of insect physiology, 2008)
The cephalic region of the labial gland in the buff-tailed bumblebee, Bombus terrestris, consists of numerous acini (formed by associated secretory cells and a central lumen) and connecting ducts. Age-dependent changes in secretion production (both qualitative and quantitative) are associated with changes in the amount of rough endoplasmic reticulum (RER), Golgi apparatus, and smooth endoplasmic reticulum (SER). The main secretory organelle is RER in the youngest individuals (pharate, and less-than-a-day old males), Golgi apparatus in 1-day-old males, and SER in males older than 2 days. Secretory cell death starts at 5 days of age, with maximal longevity to 10 days. Pheromone production starts immediately after eclosion, with pheromone quantities increasing until day 7. 2,3-dihydrofarnesol, the main component of the male-marking pheromone, appears in 1-day-old male glands, and reaches a maximum at 7 days of age, when its presence in the gland starts to decrease gradually. Older glands contain compounds not present in young ones. Variation in pheromone quantity and composition are reflected sensitively in the response of the queen antennae. Though queen antennae responded to gland extracts of all ages examined, maximum sensitivity was observed in response to extracts of glands 2-10 days old, while extracts of older glands gradually lose their effectiveness. Both major and minor components of the labial gland secretion extract elicited queen antennal responses suggesting that the pheromone is a multicomponent blend. Age-dependent changes in pheromone production, accumulation and tuning of pheromone activity are all synchronized approximately with male flight from the hive.
Keywords: Sex Attractants; Ultrasonography; Exocrine Glands; chromatografie plynová; Male; Electrophysiology; Bees; Age Factors; sexuální lákadla; mužské pohlaví; včely; exokrinní žlázy; Chromatography, Gas; Animals; elektrofyziologie; Microscopy, Electron, Transmission; zvířata; věkové faktory; transmisní elektronová mikroskopie; ultrasonografie